The Use of Refuse Derived Fuel (RDF) in the Power Industry (Agricultural Engineering, 2020)
The paper presents the concept of use of fuels produced from production waste (RDF). The usefulness of RDF processed into pellets used in the chemical and power industry was also analyzed. The paper presents the results of research on the quality and content of selected elements in RDF pellets. The values of individual indexes are within the ranges typical for fuels manufactured from plastics. The tested material’s humidity was identified as low, as well as the content of chlorine, sulfur and other elements. In the working condition, the calorific value of the tested sample was 25.260 MJ·kg−1 and was above the range of typical values for RDF (13-20 MJ·kg−1). The moisture content in the tested material was 1% and it was within the required range. In the laboratory tests, the content of chlorine and sulfur was also determined.